2021
DOI: 10.1093/g3journal/jkab078
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes involved in cuticular hydrocarbon differentiation between cryptic, parabiotic ant species

Abstract: Insect cuticular hydrocarbons (CHCs) are highly diverse and have multiple functions, including communication and waterproofing. CHC profiles form species-specific, complex blends of up to 150 compounds. Especially in ants, even closely related species can have largely different profiles, raising the question how CHC differences are mirrored in the regulation of biosynthetic pathways. The neotropical ants Crematogaster levior and Camponotus femoratus both consist of two cryptic species each that are morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…CHC differences might also occur due to assortative mating and have been found to be correlated with speciation events in other insects (Schwander et al, 2013;Chung and Carroll, 2015). Moreover, CHC profiles have frequently been found as the first and most characteristic phenotypic traits to diverge between populations and evolutionarily young species pairs (Espelie et al, 1990;Raychoudhury et al, 2010;Sprenger et al, 2021). Therefore, it is surprising that we could not detect any congruent CHC divergence separating the two postulated N. vitripennis ecotypes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…CHC differences might also occur due to assortative mating and have been found to be correlated with speciation events in other insects (Schwander et al, 2013;Chung and Carroll, 2015). Moreover, CHC profiles have frequently been found as the first and most characteristic phenotypic traits to diverge between populations and evolutionarily young species pairs (Espelie et al, 1990;Raychoudhury et al, 2010;Sprenger et al, 2021). Therefore, it is surprising that we could not detect any congruent CHC divergence separating the two postulated N. vitripennis ecotypes.…”
Section: Discussionmentioning
confidence: 76%
“…CHC profiles have repeatedly been demonstrated to diverge rapidly in populations according to different ecological conditions (Menzel et al, 2017;Menzel et al, 2018;Hartke et al, 2019). Furthermore, CHC profiles have the potential to be utilized as chemotaxonomic traits to successfully discriminate otherwise indistinguishable sympatric populations of a single species (Takahashi et al, 2001;Everaerts et al, 2008) or recently diverged sister species (Finck et al, 2016;Sprenger et al, 2021). Notably, CHC profiles were the most apparent phenotypic traits clearly distinguishing the two most recently diverged species of the Nasonia genus, N. giraulti and N. oneida (Raychoudhury et al, 2010;Werren et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The assessment of transcript counts as approximation of the actual genomic repertoire for CHC biosynthesis genes naturally has its limits and will remain speculative until targeted knockdown studies confirm the actual functions of the transcripts as well as their underlying genes. However, analyzing the abundance of unique transcripts per ortholog allows valuable insights into functional diversity potentially exceeding the information contained within whole-genome sequences (He et al 2021;Sprenger et al 2021). Correlating transcriptomic diversity directly with CHC profile variation has been attempted surprisingly rarely despite its potential to approximate the genetic control of CHC variation more accurately, as it has repeatedly been shown that the same genotype can produce different CHC profiles (Holze et al 2021;Sprenger et al 2021).…”
Section: Chc Biosynthesis Gene Transcript Variation Across the Studie...mentioning
confidence: 99%
“…However, analyzing the abundance of unique transcripts per ortholog allows valuable insights into functional diversity potentially exceeding the information contained within whole-genome sequences (He et al 2021;Sprenger et al 2021). Correlating transcriptomic diversity directly with CHC profile variation has been attempted surprisingly rarely despite its potential to approximate the genetic control of CHC variation more accurately, as it has repeatedly been shown that the same genotype can produce different CHC profiles (Holze et al 2021;Sprenger et al 2021). Thus, our findings constitute promising first steps for future studies with the potential to corroborate our transcriptomic assessment with target gene counts once further genomic resources become available.…”
Section: Chc Biosynthesis Gene Transcript Variation Across the Studie...mentioning
confidence: 99%
“…However, the emergence of cuticular hydrocarbon (CHC) profiling has emerged as a useful chemotaxonomic tool over the past few decades [4]. These compounds are endogenously synthesized by nearly all insects and exported to the cuticle [5,6], with one of their major functions being to mediate communication with other insects. Consequently, there is a wide range of diversity in CHC profiles, which is reflective of the genetic diversity of the species in question.…”
Section: Introductionmentioning
confidence: 99%